Exploring Doping Awareness: Medical Experts’ Perspectives and Their Commitment to Doping Prevention - Vanya Rangelov Kozhuharov; Radiana Staynova; Kalin Ivanov; Hristo Manev; Stanislava Ivanova (Pharmacy)
Humanity has used and explored various performance-enhancing remedies since ancient times. To protect clean sport, athletes’ health, and to provide fair and transparent competitions, different anti-doping policies were implemented. Nowadays, the anti-doping policies are evolving every year and are governed by the World Anti-Doping Agency. The use of doping in sports is regarded as a persistent problem across various athletic disciplines; at the same time, the topic of whether doping is preventable is highly discussed. The aim of this study was to assess the knowledge of medical specialists about doping compounds and to analyze their willingness and preparedness to participate in doping prevention programs. A cross-sectional questionnaire-based study was conducted between March 2024 and May 2024. Study participants included medical and pharmacy students, pharmacists, and medical doctors. Statistical analysis was performed using IBM SPSS Statistics version 24.0. Descriptive statistics, one-way analysis of variance (ANOVA), and independent-samples t-test were applied to analyze different variables. The results from the study suggested that healthcare professionals, particularly pharmacists, could be successfully engaged in doping prevention. Additionally, community pharmacies could also be involved in doping-prevention strategies since they are recognized as easily accessible healthcare locations. The relationship between medical specialists and professional athletes is essential for raising awareness, receiving trustworthy information, and developing decision-making capability to prevent not only the intentional but also the unintentional anti-doping rule violations.